ANALISIS KEGIATAN STIMULASI KESEIMBANGAN TUBUH ANAK USIA 3-4 TAHUN DI RW 02 KELURAHAN LESANPURO MALANG - Dhevira Ayu Ashandi; Pramono; Astuti, Wuri (PG PAUD Universitas Negeri Surabaya, 2021)
This research was carried out aimed at analyzing children's body balance activities in RW 02 Lesanpuro. The study used a qualitative descriptive method, which is a research procedure that uses descriptive data in the form of written or spoken words from the object being observed. This study shows the supporting and inhibiting factors of balance stimulation in the RW 02 Lesanpuro area, the supporting factors are found in the RW 02 environment with a place that is good enough for children to develop aspects of balance by playing, and inhibiting factors are shown from statements of parents who do not provide stimulation. for some reason.